THE RELATIONSHIP BETWEEN TEACHER PERFORMANCE AND LEARNING ACHIEVEMENT DURING THE COVID PANDEMIC 19 STUDENTS IN CLASS V SDN BAMBALEMO - Nurlina Nurlina; Asriani Asriani (Universitas Tadulako, 2021)
Based on the results of observing problems at SDN Bambalemo, teachers have different performances. In learning teacher performance is very influential for students. With the teacher's performance, students are not willing to do undesirable actions such as undisciplined, disrespectful and respectful of the teacher when speaking in front of the class. In addition, there are also teachers at SDN Bambalemo whose performance is less than optimal in carrying out the learning process in the classroom such as being late for class, less encouraging and guiding when students do not understand the learning material being taught so that students do not progress in their learning achievement, it is performance. the teacher decreases the learning achievement of their students. The purpose of this study was to see the relationship between teacher performance and student achievement during the Covid19 pandemic. This research is a qualitative descriptive type of research that describes or describes the relationship between variable X (teacher performance) and variable Y (student learning achievement). The results of this study were seen from the achievement classification teacher performance criteria where of the 31 students who became respondents there were 15 students or 48.39% who stated that the performance of teachers at SDN Bambalemo was sufficient, 16 students or 51.61% stated that the teacher performance was less. Student learning can be seen from the classification of achievement where of the 31 students who became respondents there were 13 students or 41.93% who stated that student learning achievement was sufficient and 18 students or 58.07% stated that student achievement at SDN Bambalemo was lacking. Based on the data obtained in the field, it shows a serious relationship between teacher performance and student achievement, this is evidenced by the low questionnaire data on teacher performance, learning achievement and the acquisition of student report cards.